If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(p + -3) = 5(p + -1) Reorder the terms: 3(-3 + p) = 5(p + -1) (-3 * 3 + p * 3) = 5(p + -1) (-9 + 3p) = 5(p + -1) Reorder the terms: -9 + 3p = 5(-1 + p) -9 + 3p = (-1 * 5 + p * 5) -9 + 3p = (-5 + 5p) Solving -9 + 3p = -5 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -9 + 3p + -5p = -5 + 5p + -5p Combine like terms: 3p + -5p = -2p -9 + -2p = -5 + 5p + -5p Combine like terms: 5p + -5p = 0 -9 + -2p = -5 + 0 -9 + -2p = -5 Add '9' to each side of the equation. -9 + 9 + -2p = -5 + 9 Combine like terms: -9 + 9 = 0 0 + -2p = -5 + 9 -2p = -5 + 9 Combine like terms: -5 + 9 = 4 -2p = 4 Divide each side by '-2'. p = -2 Simplifying p = -2
| 132.49/15=192.49 | | 10+6x-3x=10 | | 8x^2-11x+56=0 | | 5th=135 | | 10x8/5 | | x-20+2x=35 | | 3(x+5)-4-3x= | | 5z-2=6z | | 5n+3(2n-8)=2(n+6) | | 4N+32=3N | | 6(-.5)+1=m | | 4/5x-12=-32 | | -5x-8+3x=-18 | | -3x^2+18x-27=0 | | .6x-21=15 | | .3x-4=.75x+1 | | 3x+5=3x+55 | | 6x-3(2x+2)=2x-3 | | 3x+2(2x+15)=107 | | 4.5/(g+2)=3/(0.5g-1) | | 6(6v+5)=14+5v | | 0.5=0.4y-0.25(90) | | 45+60x= | | 12x=4x+2 | | 3x(2-3)=x | | 3(-.5)-(-.5+1)=x | | 4(n-1)-(4-9n)=12n | | .08x=.03(x+200)-4 | | -x-5=13 | | (x-5)(x+6)/(x-3)=0 | | 3x+(2x+15)=107 | | 10(5+x)=14(y-3) |